Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
UNLABELLED: Rapid quantification of Mycobacterium tuberculosis (Mtb) is important for monitoring bacterial load during treatment and in clinical studies. The molecular bacterial load assay detecting Mtb 16S ribosomal RNA (TB-MBLA) can quantify mycobacterial load within hours. As the current TB-MBLA protocol includes highly toxic chemicals and manual RNA extraction, we aimed to optimize TB-MBLA for routine clinical laboratories. We compared several strategies to inactivate Mtb in sputum samples, which would facilitate analysis outside a BSL3 laboratory. Heating at 80°C for 20 min was the most efficient inactivation strategy, whereas GTC-DTT and 1 M NaOH failed to inactivate Mtb sufficiently. We used Mtb-inoculated sputum samples to compare manual phenol-chloroform RNA extraction, as recommended by the TB-MBLA protocol, to an automated magnetic bead-based extraction. Automated RNA extraction reduced total analysis time by 2 h and performed equally to phenol-chloroform extraction, with a detection limit of close to 100 CFU in 10-fold dilution series (mean Ct value: 36.0 ± 1.4 automated versus 33.5 ± 3.6 manual, n = 6). Freezing samples in lysis buffer up to 14 days did not affect TB-MBLA performance (mean Ct value: 22.6 ± 0.3 fresh versus 22.6 ± 0.6 frozen, n = 6). The final TB-MBLA protocol quantified bacterial load up to 11 days faster than time-to-positive culture (TTP) (mean TTP: 11 days, 2-24 days, n = 9) in sputum from patients with pulmonary TB. We adapted the TB-MBLA method for faster throughput in a routine clinical laboratory by using inactivation at 80°C for 20 min, followed by automated RNA extraction, achieving equal sensitivity compared to the original TB-MBLA method, and avoiding manual extraction and toxic reagents. IMPORTANCE: The current tuberculosis molecular bacterial load assay (TB-MBLA) protocol relies on toxic chemicals and manual RNA extraction, making the procedure both time‑consuming and labor‑intensive. We optimized and validated a faster TB-MBLA strategy, which can be adapted for routine clinical laboratories, including inactivation by heating, to facilitate implementation in settings without a BSL3 laboratory.